Toward a Growth-Oriented Model of Financial Programming. (IMF Working Papers; Working Paper ;, 1987)
This paper extends the basic monetary model that underlies the monetary approach to the balance of payments to allow for the endogenous determination of the short-run growth rate of the economy. In the extended model domestic credit expansion affects not only the balance of payments but also the output growth rate, which bears implications for the formulation of credit ceilings. Furthermore, the amount of external financing can influence both the output growth rate and the balance of payments outcome, unlike with the basic model. An integrated treatment of exchange rate adjustment involving both absorption and elasticity effects is provided.